The Subject of Religion: Lacan and the Ten Commandments - Reinhard, Kenneth; Lupton, Julia Reinhard (Diacritics, 2003)
Reinhard and Lupton reconstruct the subject of religion by reading Lacan's commentary on the Decalogue through hermeneutical openings provided by the exegetical history of the Ten Commandments. By locating the subject of religion in the negative intersection between culture and philosophy, they indicate directions for a Lacanian criticism beyond the twin lures of social realism and theoretical idealism.